A GPRS-based wearable electronic thermometric alarm system - Huisheng Zhang; Ruikai Zhang; Qiaoliang Li; Li Yin; Siping Chen; Tianfu Wang; Shumei Lin; Xinyu Liu; Xiaofei Zhang; Xi Chen (2012 5th International Conference on Biomedical Engineering and Informatics, 2012)
Body temperature is a crucial vital sign, detecting and recording patients' body temperature can be very helpful for diagnosis and treatments. The widely used thermometers nowadays are not capable to continuously detect body temperature, and the geographic range of data transmission is also restricted. This paper develops a GPRS-based wearable thermometric alarm system that can monitor patients' body temperature 24-hour continuously. A low power MSP430 microcontroller is used to collect data from a high accuracy thermistor and control a MC55 GPRS module for remote data transmission. People can register their cell phone number to the system and get body temperature measurement results. This paper presents how we design a light weighed, small and low power consumption device. The device can be used in various situations such as patients' temperature monitoring at hospital and children's temperature monitoring at school. It has a broad practical usage and a promising market future.